ETNOGRAFI KURIKULUM SEKOLAH ALAM: ANTARA KEBEBASAN DAN CAPAIAN PEMBELAJARAN - Okta Rosfiani; Amatillah, Afifah Afra; Faatihah Oktavia Priislami; Ilham Nur Rifqi; Muhammad Juan Alfaridzi; Najwa Hamid; Cecep Maman Hermawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This ethnographic research aims to describe and analyze the construction of the natural school curriculum, learning practices that reflect freedom and achievement of learning targets, as well as strategies used by teachers and school administrators in balancing these two aspects. The research employed a qualitative approach with ethnographic methods at Sekolah Alam Depok, involving principals, teachers, students, and school administrators as research subjects. Data collection techniques included participatory observation, in-depth interviews, and documentation, with data validity guaranteed through source triangulation, method triangulation, extended participation, and member checks. Data analysis used the Spradley model consisting of domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The findings reveal that Sekolah Alam Depok implements the Selaras Curriculum which integrates national curriculum competencies, IB curriculum, and Tauhidi curriculum mapped into four main pillars: science logic for academic aspects, morals as a hidden curriculum for character building, leadership for life skills, and business for economic independence. The learning methodology highly appreciates autonomy and learning freedom, with teachers acting as facilitators. The PUP assessment system (Assignment for Understanding Demonstration) has shifted from formal summative exams to daily formative assessments. The findings also indicate challenges regarding equivalence of achievement with formal schools, particularly for students targeting transition to public high schools. This research contributes to the development of alternative curriculum and pedagogical studies, as well as practical benefits for natural school administrators, teachers, and education policymakers in formulating more contextual and responsive curriculum approaches to student needs.